Strongyloides ratti : Identification, isolation and characterisation of Heat Shock Protein 10 and Heat Shock Protein 60 - Tazir, Yasmina; Justus Liebig University Giessen (My University, 2009)
S. stercoralis and S. ratti are intestinal parasitic nematodes infecting humans and rats. Both nematodes present extraordinary life cycles, comprising a free-living generation in addition to parasitic stages. To better understand the parasite?host relationship, the study of host defence?modulating molecules in parasitic systems may likely reveal new principles of their function. In search of such molecules, we performed mass spectrometry to identify excretory/secretory products of S. ratti. Among others, homologues of the heat shock proteins HSP10 and HSP60 (SrHSP10, SrHSP60) were detected. Intensive study of immune functions of HSP10 and HSP60 within the last years clearly demonstrated that they possess immune stimulatory potential and hence suggest additional roles to their protein folding function in parasite biology. To characterise SrHSP10 and SrHSP60, their full-length cDNA were cloned, the genomic organisation analysed, their presumptive role as interaction partners investigated, their tissue-specific transcription studied, and SrHSP10 was expressed for antibody production. Based up on these results, the protective potential of SrHSP10 was investigated by immunological studies. The SrHSP10 cDNA contains an open reading frame of 330 bp, encoding a polypeptide of 110 amino acids with an approximate molecular weight of 10 kDa. The resulting full length SrHSP60 cDNA is 1914 bp in size. The deduced amino acid sequence has a predicted molecular mass of 64 kDa. Both proteins exhibit high homology to that of the human pathogen S. stercoralis. The analysis of the genomic organisation of the SrHSP10 and SrHSP60 locus revealed that the genes are linked in a head-to-head configuration by a bidirectional promoter. Mammalian and yeast two-hybrid assays correspondingly showed dimerisation of SrHSP10. In situ hybridisation results demonstrated SrHSP10 transcription in the complete gut area. Immunisation experiments, finally, revealed a high immunogenicity of SrHSP10 and provided evidence for a strong protective effect in S. ratti-infected rats.
Keywords: ddc:630